Simultaneous Integrated Boost Intensity-Modulated Radiation Therapy Can Benefit the Locally Advanced Rectal Cancer Patients With Clinically Positive Lateral Pelvic Lymph Node - Li, Shuai; Zhang, Yangzi; Yu, Yang; Zhu, Xianggao; Geng, Jianhao; Teng, Huajing; Wang, Zhilong; Sun, Tingting; Wang, Lin; Wang, Hongzhi; Li, Yongheng; Wu, Aiwen; et al. (Frontiers in Oncology, 2021)
Abstract Background and Purpose: The optimal treatment modality for clinically positive lateral pelvic lymph node (LPLN) from locally advanced rectal cancer (LARC) is unknown. Thus, we aimed to analyze the optimal radiotherapy dose for clinically positive LPLN from LARC. Materials and methods: We retrospectively evaluated distal LARC (i.e., within 8 cm from the anal verge) patients with clinically positive LPLN (i.e., ≥7 mm in the short axis). They were divided into two groups based on whether or not they received simultaneous integrated boost intensity-modulated radiation therapy (SIB-IMRT)–based chemoradiotherapy. The total radiotherapy dose on LPLN were 56-60Gy for SIB-IMRT group and 41.8Gy for non-SIB-IMRT group. The clinical parameters and regrowth rate of LPLN were then compared between the two groups. Results: A total of 151 patients were evaluated, and 83 and 68 patients were classified to the SIB-IMRT and non-SIB-IMRT group, respectively. The median follow-up period was 22.6 months, and the 2-year LPLN regrowth rate was significantly different between the SIB-IMRT group and the non-SIB-IMRT group (0% vs 10.8%, P=0.024). Further, SIB-IMRT yielded a significantly lower 2-year LPLN regrowth rate in patients whose LPLN measured ≥8 mm in the short axis (0% vs. 15.9%, P=0.019) or ≥10 mm in the long axis (0% vs. 17.6%, P=0.024) compared to patients who were in non-SIB-IMRT group. Meanwhile, there was no significant difference in grade II radiation-related toxicity (30.1% vs. 39.1%, P=0.217) and surgical complications (21.8% vs. 12.2%, P=0.198) between the two groups. Conclusion: SIB-IMRT–based neoadjuvant chemoradiotherapy is beneficial for eliminating clinically positive LPLN from LARC without increasing the incidence of radiotherapy-related toxicity and surgical complications, and patients with larger LPLN may gain benefit from this technique.